(untitled) (The International Journal for Scientific Research, 2023)
The study aims to identify the number of tweets concerned with the political empowerment of Saudi women through the accounts of tweeters on the (x) platform, and the network analysis of the accounts of women leaders to monitor the number of nodes and links on political empowerment topics through the (x) platform. The study belongs to descriptive explanatory studies and relies on the network analysis methodology. The study used network analysis in data collection, analysis and interpretation, by applying to a sample of (5) accounts of women leaders in Saudi society through the (X) platform, namely: (Hala Al-Tuwaijri - Kawthar Al-Arbash - Haifa Mohammed Al Saud - Amal Yahya Al-Muallimi - Adwaa Abdul Rahman Al-Arifi) were withdrawn during October 2023, with a total of (1274) tweets, relying on the theory of network analysis as a theoretical framework for the study. The study reached a set of results, most notably: It was found that there is a large state of activity and interaction in the accounts of women leaders in the Kingdom of the study sample through the (X) platform, where the presence of tweets of a large number of users commenting on what is published during the study period, and this is clearly shown by the high number of tweets. The account of (Amal Yahya Al-Moallimi) was distinguished from the rest of the accounts of the study sample, in the emergence of words indicating the political empowerment of women, the most prominent of which came (ambassador), (diplomacy), and (leadership). With regard to the most prominent forms of interaction with tweets on the accounts of women leaders, the form of interaction (showing likes) came at the forefront of the forms of interaction between the five accounts of the study sample. The study recommends the need to increase attention to the political empowerment of Saudi women, by opening more areas of discussion on topics of political empowerment through various media, especially through social networking sites and applications, in light of the Kingdom’s direction in its ambitious Vision 2030.